2022
DOI: 10.21203/rs.3.rs-1740732/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spiritual well-being correlates with quality of life of both cancer and non-cancer patients in palliative care -further validation of EORTC QLQ-SWB32 in Finnish

Abstract: Background: The European Organisation for Research and Treatment of Cancer (EORTC) has developed the Spiritual Well-being Questionnaire (EORTC QLQ-SWB32) for assessment of spirituality in palliative care for cancer. We aimed to translate and validate this tool in Finnish and to study the relationship between spirituality and quality of life (QOL). Methods: Finnish translation was produced according to the guidelines of EORTC and included forward- and back-translations. Face-, construct- and convergence/diverge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
1
0
1
Order By: Relevance
“…Studies indicate that spiritual well-being is related to better quality of life and lower incidence of physical and emotional symptoms. A recent study in Finland showed a correlation between spiritual well-being and quality of life in patients with and without cancer eligible for palliative care ( 10 ) . Another cross-sectional study in Portugal, with 95 patients receiving palliative care, reported that spiritual well-being was significantly correlated with higher levels of physical, emotional and functional well-being, in addition to better quality of life ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that spiritual well-being is related to better quality of life and lower incidence of physical and emotional symptoms. A recent study in Finland showed a correlation between spiritual well-being and quality of life in patients with and without cancer eligible for palliative care ( 10 ) . Another cross-sectional study in Portugal, with 95 patients receiving palliative care, reported that spiritual well-being was significantly correlated with higher levels of physical, emotional and functional well-being, in addition to better quality of life ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Estudos indicam que o bem-estar espiritual está relacionado à melhor qualidade de vida e menor incidência de sintomas físicos e emocionais. Um estudo recente na Finlândia mostrou correlação entre o bem-estar espiritual e a qualidade de vida em doentes com e sem câncer elegíveis para cuidados paliativos (10) . Outro estudo transversal em Portugal, com 95 doentes com cuidados paliativos, relatou que o bem-estar espiritual se correlacionou significativamente com níveis mais elevados de bem-estar físico, emocional e funcional, além de melhor qualidade de vida (11) .…”
Section: Introductionunclassified